Identifikasi Batuan Reservoir Panas Bumi di Daerah Tambang Sawah, Lebong Provinsi Bengkulu Menggunakan Data Gravitasi Satelit GGMPlus dengan Inversi 2D - Hardianza, Meno; Hadi, Arif Ismul; Hilmi Zakarya (Universitas Andalas, 2025)
The Tambang Sawah geothermal field located in Lebong Regency, Bengkulu Province, is one of the geothermal energy potentials in Indonesia. The area is associated with tectonic activity in the bukit barisan mountain range which is indicated by the appearance of hot springs and fumaroles. This research uses Global Gravity Model (GGM) gravity data, in the form of Free Air Anomaly (FAA) data with a resolution of 220 metres and shuttle radar topography mission (SRTM2Gravity) as contemporary terrain correction data in the form of full scale gravity data. The FAA data was then subtracted from the full scale gravity data to obtain the complete Bouger anomaly (CBA). The CBA was subjected to spectrum analysis to determine the depth estimate and then separated to obtain regional and residual anomalies using the moving average method. There are three distribution patterns of anomaly distribution, namely low, medium and high. The results showed that on the CBA map, areas with moderate anomalies were thought to have geothermal reservoirs with densities < 2.53 g/cm3 different depths.